ANALISIS RASIO KEUANGAN PADA PT. PEGADAIAN (PERSERO) PERIODE 2017 - 2021 - Lamhot Rejeki, (2023)
Financial ratio analysis is an activity that shows mathematically between amounts and other amounts. Financial ratios are used to evaluate company performance and compare it with standard ratio comparisons. Financial ratio analysis provides insight into a company's financial position, financial health, operational efficiency, and rate of return on investment. By using financial ratios, company management can identify strengths and weaknesses in financial performance. For this reason, companies must be able to survive and even grow and develop properly, namely by paying attention to the conditions of their companies and adapting to increasingly rapid technological advances. To find out how the condition of a company requires good analysis, so that the company can make the right decision. The purpose of this final project is to understand, study and find out the financial performance of PT. Pegadaian (Persero) 2017 - 2021 based on financial ratio analysis consisting of liquidity, activity, solvency and profitability ratios using indicators in the Decree of the Minister of State-Owned Enterprises KEP-100/MBU/2002. The results of this writing will determine the health of the company's performance in each position Return On Equity (ROE), Return On Investment (ROI), Cash Ratio, Current Ratio, Collection Period, Inventory Turnover, Total Asset Turn Over (TATO), Ratio of Total Own Capital to Total Assets ( TMS Against TA).